Efficient Microwave-Assisted Synthesis of N-(tert-Butylsulfinyl)imines Catalyzed by Amberlist-15 - Sanaboina, Chakrapani; Jana, Samaresh; Eppakayala, Laxminarayana (Synlett, 2014)
A general and efficient methodology is reported for the synthesis of N-(tert-butylsulfinyl)imines by using the heterogeneous catalyst amberlist-15, under microwave irradiation. Amberlist-15 is easy to handle, safe to use and quickly separable from the reaction mixture. This method offers a number of advantages including operational simplicity, inexpensive catalyst, high yield of products, and broad substrate scope.
Keywords: imines; building blocks; microwave; heterogeneous catalyst; aldehydes